Delivery of FGF18 using mRNA-LNP protects the cartilage against degeneration via alleviating chondrocyte senescence - Keyu Kong; Baixing Li; Yongyun Chang; Chen Zhao; Hua Qiao; Minghao Jin; Xinru Wu; Wenxuan Fan; Liao Wang; Yansong Qi; Yongsheng Xu; Zanjing Zhai; et al. (Journal of Nanobiotechnology)
Abstract Background Osteoarthritis (OA) is a degenerative joint disease with an immense unmet medical need. FGF18 protein is a potential regenerative factor for cartilage repair. However, traditional protein delivery methods have limited efficacy due to the short lifetime and shallow infiltration. Results In this work, we discovered that lipid nanoparticle (LNP) can infiltrate and deliver FGF18 mRNA deeper in the cartilage than proteins. After mRNA UTR optimization and chemical modification, the expression of FGF18 can last up to 6 days in the cartilage. Furthermore, delivering FGF18 mRNA activates FOXO3a-autophagy pathway, which protects against chondrocyte degeneration and senescence. Local intra-articular injection of FGF18 mRNA-LNP significantly alleviates OA symptoms in DMM and senile OA models. Sustained expression and accessibility of FGF18-mRNA to deeper chondrocytes makes LNP-mRNA more effective than FGF18 recombinant protein. Conclusions In summary, this study presents a novel approach superior to recombinant protein alone and holds promise as a new therapeutic strategy for OA. Graphical abstract